DUKUGAN GEORGE W. BUSH Jr TERHADAP ISRAEL (2000-2009) - Davit Romansa (HI 16 UMY 079, 2016)
*79 This journal has the purpose to explain the American attitude in making foreign policy post 9/11 WTC terror during the former US president George W. Bush. American foreign policy post-WTC seem very aggressive and protect the interests of Isreael. A foreign policy that made the United States government can not be separated from the influence of George W. Bush as a supreme actor makers policy makers. By using the constructivist theory, the author would like to explain the role of George W. Bush personally in making the decision of American foreign pro-Israel, which turned out measures taken Bush is influenced by the environment around Bush. With the influence of the Jewish environment around Bush is the reason that every policy during the Bush period has always impressed protecting the interests of Israeli Jews. Keywords: George W. Bush, Policy, Israel, Perseption